INTERMITTENT FASTING AND CHRONONUTRITION: SYNERGISTIC APPROACHES FOR METABOLIC HEALTH - Mariani, Andressa dos Reis Gonçalves (Revista Sistemática, 2023)
Intermittent fasting (IF) and chrononutrition are emerging dietary strategies that align eating patterns with human circadian rhythms to improve metabolic health. While intermittent fasting emphasizes extended periods without caloric intake, chrononutrition focuses on the timing of food consumption relative to biological clocks. Both approaches have been associated with improvements in insulin sensitivity, lipid metabolism, and weight management. Evidence suggests that meal timing plays a critical role in regulating circadian physiology, influencing hormone secretion, glucose metabolism, and energy expenditure. Integrating principles of IF and chrononutrition may provide synergistic benefits for obesity prevention, metabolic syndrome management, and long-term health. This article reviews the scientific basis of intermittent fasting and chrononutrition, explores their mechanisms of action, and discusses their potential applications in clinical and public health contexts.